2009
DOI: 10.1073/pnas.0900408106
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IL-17-producing FOXP3+regulatory T cells in humans

Abstract: IL-17-producing CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
542
4
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(587 citation statements)
references
References 42 publications
34
542
4
5
Order By: Relevance
“…Accumulating evidence shows that human regulatory T cells show plasticity and may differentiate IL-17-producing cells (23)(24)(25)(26)(27). In the presence of IL-6, the inhibition of RORC2 by FOXP3 is abrogated, and IL-17 production is seen in regulatory T cells still expressing FOXP3 mRNA (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accumulating evidence shows that human regulatory T cells show plasticity and may differentiate IL-17-producing cells (23)(24)(25)(26)(27). In the presence of IL-6, the inhibition of RORC2 by FOXP3 is abrogated, and IL-17 production is seen in regulatory T cells still expressing FOXP3 mRNA (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
“…In the presence of IL-6, the inhibition of RORC2 by FOXP3 is abrogated, and IL-17 production is seen in regulatory T cells still expressing FOXP3 mRNA (23)(24)(25). CCR6-expressing regulatory T cells possess suppressive function, although they produce IL-17 upon activation (26). IL-2 and IL-15 have been shown to induce the differentiation of human regulatory T cells into IL-17-producing cells, and this is further enhanced in particular when exogenous IL-1b, IL-23, or IL-21 is present (27).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, IL-17-producing Foxp3 þ T cells were identified in peripheral blood as well as in the microenvironments of chronic inflammation and cancer. 23,[45][46][47] Although most of these studies indicated that human Foxp3 þ IL-17 þ cells retain regulatory capacity as long as they express Foxp3, it was suggested that they can foster the expression of proinflammatory cytokines and thus behave as ''inflammatory'' Tregs. 23 In addition, in vitro studies showed that human RORgt þ Th17 cells preferentially differentiate from naïve Foxp3 þ T cells that lose their Foxp3 expression 48 that may eventually lead to conversion into pathogenic Th17 cells under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies in humans and mice have identified cell subsets, which coexpress the Treg master transcription factor Foxp3 and the Th17 cell-related transcription factor RORgt. 28,29 Therefore, RORgt + Foxp3 + double-positive cells, which might differentiate into Th17 cells under inflammatory conditions, could have been depleted in DEREG mice upon injection of diphtheria toxin in our recent study. In line with this, we were able to detect a distinct renal Foxp3 + IL-17 + T cell population in nephritic mice via flow cytometry (data not shown).…”
Section: Discussionmentioning
confidence: 99%